2010
DOI: 10.1007/s00198-010-1425-9
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein predicts incident fracture in community-dwelling elderly Japanese women: the Muramatsu study

Abstract: CRP is a significant predictor of osteoporotic fracture in elderly Asian women who have substantially lower CRP levels than Caucasians. Mechanisms explaining such an association should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 29 publications
(39 reference statements)
4
43
1
Order By: Relevance
“…Hip fracture risk was not associated with CRP. Our results differ from previous studies reporting that the risk of fracture increases with higher CRP [20,22,23,31]. Schett et al found a higher relative risk for non--traumatic fractures in the highest vs. the lowest tertile of CRP in a middle aged population [24] and similarly, Eriksson et al…”
Section: Discussioncontrasting
confidence: 99%
“…Hip fracture risk was not associated with CRP. Our results differ from previous studies reporting that the risk of fracture increases with higher CRP [20,22,23,31]. Schett et al found a higher relative risk for non--traumatic fractures in the highest vs. the lowest tertile of CRP in a middle aged population [24] and similarly, Eriksson et al…”
Section: Discussioncontrasting
confidence: 99%
“…(16) Rolland et al reported that men with the highest levels of CRP had higher odds for prevalent fracture than men with lower levels of CRP, but CRP levels were not associated with BMD at any site. (21) An interesting finding in that study was that higher CRP levels were associated with lower trabecular BMD, lower trabecular number and larger trabecular separation at the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between levels of CRP and bone mineral density (BMD) is conflicting. (16,21,24,25) A recent study showed that CRP was not associated with femoral neck and lumbar spine BMD, but inversely associated with bone strength index, which partially explained the increased fracture risk that was associated with inflammation. (17) We hypothesized that higher levels of CRP increase the risk of nonvertebral fracture in Tromsø, a population with a high incidence of fracture, and we aimed to test whether CRP is an independent risk factor for non-vertebral fractures, and whether CRP is associated with BMD, in both genders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 High serum levels of proinflammatory cytokines, cytokine-soluble receptors, and C-reactive protein have been associated with increased risk of fractures. [9][10][11][12] The immune system influences differentiation and activity of bone cells within the bone microenvironment. 13,14 Thus, in this study, we aimed to evaluate Trp degradation and clarify whether altered levels of Kyn/Trp ratio could be correlated to osteoporotic hip fractures via immune system.…”
mentioning
confidence: 99%